Principle of legal certainty of power of attorney imposing mortgage rights as credit guarantee for micro, small and medium enterprises - Lilawati Ginting (Lembaga Riset Mutiara Akbar, 2026)
A Power of Attorney to Impose a Mortgage (Surat Kuasa Membebankan Hak Tanggungan / SKMHT) is a legal instrument commonly used in banking practices as collateral for Micro, Small, and Medium Enterprises (MSMEs) credit, particularly when the establishment of a Mortgage Right (Hak Tanggungan) cannot be carried out immediately. The use of SKMHT is intended to accelerate credit disbursement and provide administrative convenience for MSMEs. However, since SKMHT merely grants authority and does not constitute a material security right, legal issues arise concerning the application of the principle of legal certainty for creditors. This study aims to analyze the implementation of the principle of legal certainty in the use of SKMHT as collateral for MSME credit. The research employs a normative juridical method with statutory and conceptual approaches. The findings indicate that the use of SKMHT in MSME credit arrangements does not fully fulfill the principle of legal certainty, as it fails to provide strong legal protection for creditors prior to its conversion into a Deed of Granting Mortgage Rights (Akta Pemberian Hak Tanggungan / APHT).